2014
DOI: 10.1166/jbn.2014.1729
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging-Visible and pH-Sensitive Polymeric Micelles for Tumor Targeted Drug Delivery

Abstract: Folate-functionalized copolymers of poly(ethylene glycol) and 2-(diisopropylamino) ethylamine grafted poly(L-aspartic acid) are synthesized. The copolymers can self-assemble into nanoscaled micelles encapsulated with hydrophobic model drug Fluorescein Diacetate (FDA) and MRI diagnostic agents superparamagnetic iron oxide nanoparticles (SPIONs) in aqueous solution of a neutral pH resembling physiological environment, whereas disassemble in acidic endosomal/lysosomal compartments of tumor cells to achieve rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Furthermore, there are polymeric micelle formulations that were designed for active targeting and modified with different ligands such as folate (binds to folate receptor). 329 In a nude mice xenograft model, doxorubicin-loaded PLGA-PEG polymeric micelle formulation was shown to increase tumor uptake and significant tumor regression. 330 These studies suggest the feasibility and utility of polymeric micelles in drug delivery for future targeted therapy applications.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…Furthermore, there are polymeric micelle formulations that were designed for active targeting and modified with different ligands such as folate (binds to folate receptor). 329 In a nude mice xenograft model, doxorubicin-loaded PLGA-PEG polymeric micelle formulation was shown to increase tumor uptake and significant tumor regression. 330 These studies suggest the feasibility and utility of polymeric micelles in drug delivery for future targeted therapy applications.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…In addition to polymeric coating, inorganic coating of magnetic nanoparticles with silica or gold has attracted attention, with regard to further surface derivatization of nanoparticles and because of their influence on colloidal stability and the biological behavior of magnetic nanoparticles in biomedical applications [11,12]. Particularly, these coated nanoparticles can be easily surface-functionalized for bioconjugation to antibodies and for targeted delivery with particle localization in a specific area [13][14][15][16]. Although various studies have reported a more efficient surface modification of magnetic nanoparticles, little work has been undertaken in this regard to systematically compare the size-dependent photodynamic anticancer efficiency among photosensitizer-coated magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is possible to adjust the peripheral chain ends of the PMs with targeting ligands in order to try to accomplish active targeting and/or pH/temperature responsive nanocarriers (Vinogradov et al 1999, Yasugi et al 1999. Therefore, the outer hydrophilic corona can be functionalized with several moieties, such as folate, monoclonal antibodies, monosaccharides (mannose, glucose, fructose), among others (Torchilin 2001, 2002, Zhang et al 2014. When the PMs have reached their targets and for the release of the drugs, degradable or stimuli-responsive micelles have been developed (Katayama et al 2001, Kumar et al 2001, Neradovic et al 2001, Kakizawa et al 1999.…”
Section: Polymeric Micellesmentioning
confidence: 99%